A study on angiotensin converting enzyme gene insertion/ deletion polymorphism in cardiovascular diseases - Ibrahim, Wisam Nabeel; A.Talib, Norlelawati; Abdullah, Nor Zamzila (2014)
Coronary artery disease (CAD) is a common disease with significantly high morbidity and mortality (Libby et al., 1998). It is also one of the leading causes of death worldwide. In 2012, it was stated that CAD participates in over 30% of Malaysian adult mortality rate (Malaysian death profile, 2013). CAD occurs from complex interactions between variety of environmental and genetic factors. Smoking, alcoholism, and sedentary lifestyle are believed to be the commonest environmental predisposing factors for CAD. On the other hand there is no strong evidence on the role of genetic factors and the extent by which they could cause this serious disease(Sinorita et al., 2010). Angiotensin converting enzyme (ACE) is an enzyme produced by the pulmonary and renal endothelial cells. This enzyme plays a key role in the production of angiotensin II and in the catabolism of bradykinin, two peptides involved in the modulation of vascular tone and in the proliferation of smooth muscle cells. Angiotensinogen, rennin, ACE, angiotensin-II and angiotensin-II receptors are primary components of rennin-angiotensin system (RAS). This system functions as the major regulator of blood pressure, fluid and electrolyte homeostasis. Disturbances among RAS components plays important role in developing hypertension & other different cardiovascular diseases (Cambien et al., 1992). Genetic variants have been identified in several components of RAS. The reported insertion/deletion polymorphism of the ACE gene has been linked with hypertension (Sayed-Tabatabaei et al., 2006). However studies on its association with other cardiovascular diseases and specially CAD are inconsistent & not well recognized